Putative Candidate Drug Targets for Sarcopenia-Related Traits Identified Through Mendelian Randomization Analysis of the Blood Proteome - Chen, Bin-Bin; Wang, Jia-Qi; Meng, Xiang-He; Luo, Zhe; Liu, Xiao-Wen; Shen, Hui; Xiao, Hong-Mei; Deng, Hong-Wen (Frontiers in Genetics, 2022)
Purpose: The increasing prevalence of sarcopenia remains an ongoing challenge to health care systems worldwide. The human proteome is a major source of therapeutic targets. Plasma proteins are functionally connected with various organs of the body to mediate overall homeostasis, thus directly regulating complex processes such as aging and the development of common chronic diseases. By performing systematic causal analysis of the plasma proteome, we attempt to reveal the etiological mechanism and discover drug targets for sarcopenia. Methods: By using data from four genome-wide association studies for blood proteins and the UK Biobank data for sarcopenia-related traits, we applied two-sample Mendelian randomization (MR) analysis to evaluate 310 plasma proteins as possible causal mediators of sarcopenia-related traits: appendicular lean mass (ALM) and handgrip strength (right and left). We also performed two-sample bidirectional MR analysis for the identified putatively causal proteins to assess potential reverse causality that the trait values may influence protein levels. Finally, we performed phenome-wide MR analysis of the identified putatively causal proteins for 784 diseases to test the possible side effects of these proteins on other diseases. Results: Five plasma proteins were identified as putatively causal mediators of sarcopenia-related traits. Specifically, leukocyte immunoglobulin-like receptor subfamily B member 2 (LILRB2), asporin (ASPN), and contactin-2 (CNTN2) had potential causal effects on ALM, and ecto-ADP-ribosyltransferase 4 (ART4) and superoxide dismutase 2 (SOD2) had putative causal effects on the handgrip strength, respectively. None of the five putatively causal proteins had reverse causality relationship with sarcopenia-related traits, and no side effects on other diseases were identified. Conclusion: We identified five plasma proteins that may serve as potential novel drug targets for sarcopenia. Our study attested to the value of this approach in identifying and prioritizing potential therapeutic targets for complex diseases.